2014
DOI: 10.2174/1389557513666131119201353
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil: An Important Prototype to the Design of New Drug Candidates for Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a progressive and incurable neurodegenerative disorder, with a dramatic socioeconomic impact. The progress of AD is characterized by a severe loss in memory and cognition, leading to behavioral changing, depression and death. During the last decades, only a few anticholinergic drugs were launched in the market, mainly acetylcholinesterase inhibitors (AChEIs), with indications for the treatment of initial and moderate stages of AD. The search for new AChEIs, capable to overcome the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…Acetyl-cholinesterase inhibitors (AChEIs), which delay the cognitive decline of AD (100), have a protective effect on the development of glaucoma. Topical rivastigmine lowered intraocular pressure (IOP) in rabbits (101).…”
Section: Visual System In Aging and Admentioning
confidence: 99%
“…Acetyl-cholinesterase inhibitors (AChEIs), which delay the cognitive decline of AD (100), have a protective effect on the development of glaucoma. Topical rivastigmine lowered intraocular pressure (IOP) in rabbits (101).…”
Section: Visual System In Aging and Admentioning
confidence: 99%
“…The FDA approved anti-Alzheimer's drug, donepezil (Aricept) is cis1-benzil-4-[5,6-dimethoxy-(1-indanone)-2-yl]-methylpiperidine hydrochloride (Figure 14, Table 4), which is reversible, non-competitive and very effective AChE inhibitor (IC 50 = 5.7 nM) with less toxicity [107,108]. This drug is clinically used for the treatment of AD in patients with mild, moderate and severe stages of cognitive impairment at maximum 23mg/day dose [107].…”
Section: Donepezil Analogsmentioning
confidence: 99%
“…The majority of novel donezepil analogs were achieved by structural modifications in these two sub-structures and the spacer. These novel donepezil analogs are discussed below [108].…”
Section: Donepezil Analogsmentioning
confidence: 99%
“…Two examples of such inhibitors are physostigmine, used to treat glaucoma, and galantamine, a drug investigated for the treatment of moderate Alzheimer's disease 24 . In the case of minaprine, an antidepressant, it was just recently shown that this drug is also a cognitive enhancer that may halt the progression of Alzheimer's disease 25 . It is thus attractive that CRANK identified minaprine as a member of a community of primarily cholinesterase inhibitors, which suggests minaprine's potential for drug repurposing for Alzheimer's disease.…”
Section: Network Of Medical Drugs With Shared Target Proteinsmentioning
confidence: 99%